War and Anti-War : Survival at the Dawn of the 21st Century - Toffler, Alvin and Toffler, Heidi (Rawalpindi, Pakistan Army Education Press, 1996)
Are we plunging into a decade of bloody wars? Can they he prevented? In this highly original new book, Alvin and Heidi Toffler, two of the world's leading social thinkers and futurists, train their sights on a subject that has haunted humanity since history began: war and peace. Their premise is that the way we make wealth is the way we make war - that today's revolutionary changes in business are being mirrored in.
Include Index, Bibliography and Notes
Keywords: Military art and science--Economic aspects